2013
DOI: 10.1177/1525740113503035
|View full text |Cite
|
Sign up to set email alerts
|

A Field Study of Telepractice for School Intervention Using the ASHA NOMS K-12 Database

Abstract: The purpose of this article is to describe the characteristics and effectiveness of a telepractice speech-language therapy program for school-age children. Outcome data related to the caseload, type and amount of intervention, and student progress from a school-based telepractice therapy program were compared with the K-12 Schools National Outcomes Measurement System (NOMS) of the American Speech-Language-Hearing Association. NOMS provides data for students receiving intervention through direct, in-person serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 16 publications
4
38
0
4
Order By: Relevance
“…Coufal et al (2018) compared connected health therapy with face-to-face therapy in a large-scale retrospective study of children between the ages of 6 and 9 years with speech sound disorders, and found no difference in outcomes between the two groups. Other studies have reported similar findings (Grogan-Johnson et al 2013, Gabel et al 2013, Lee 2018.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Coufal et al (2018) compared connected health therapy with face-to-face therapy in a large-scale retrospective study of children between the ages of 6 and 9 years with speech sound disorders, and found no difference in outcomes between the two groups. Other studies have reported similar findings (Grogan-Johnson et al 2013, Gabel et al 2013, Lee 2018.…”
Section: Introductionsupporting
confidence: 75%
“…Previous studies have found that therapy delivered via connected health had comparable results with faceto-face therapy for children with speech sound disorders (Grogan-Johnson et al 2013, Gabel et al 2013, Coufal et al 2018. In the present study, connected health was used to monitor progress, allowing the CSLT to assess the child's production of sounds and to discuss, advise and problem solve with the trained parents on the therapy process.…”
Section: Discussionmentioning
confidence: 87%
“…73 Delivery of remote speech therapy is highly acceptable to parents, 74,75 and the outcomes are comparable to in-person therapy. 76,77 Important areas to be addressed with expanding delivery of remote speech therapy include maintenance of patient relationships, interaction with parents and teachers, high fidelity technology, and ongoing training in telepractice for providers. 78 …”
Section: Innovations In Pediatric Hearing Healthcare Deliverymentioning
confidence: 99%
“…The efficacy and efficiency of telehealth speech pathology in schools, and satisfaction of parent and school staff stakeholders have been investigated [19][20][21][22] with encouraging results.…”
Section: Schools and Telehealthmentioning
confidence: 99%